2016
DOI: 10.15406/mojt.2016.02.00036
|View full text |Cite
|
Sign up to set email alerts
|

Brain Changes after Electromagnetic Fields Exposure

Abstract: In recent years, extensive knowledge about the effect of electromagnetic fields has been gathered that provided different information in accordance with the frequency waves and the type of electromagnetic fields. The present study tries to review the effects of electromagnetic fields (EMF) on brain structure and the chemical mechanisms of neurons. Previous studies suggested that Brain Changes after Electromagnetic Fields Exposure are related to areas of frontal cortex, hippocampus, basal forebrain and brainste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It is suggested that brain cholinergic system plays a crucial role in learning and on the other hand exposure to EMFs decreased activities of cholinergic system in the frontal cortex and hippocampus, both regions are involved in memory processing [7,8]. Thus, one possibility is that the impairment of cognition processing can result from decrement in transmission of cholinergic system.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that brain cholinergic system plays a crucial role in learning and on the other hand exposure to EMFs decreased activities of cholinergic system in the frontal cortex and hippocampus, both regions are involved in memory processing [7,8]. Thus, one possibility is that the impairment of cognition processing can result from decrement in transmission of cholinergic system.…”
Section: Discussionmentioning
confidence: 99%